The Election Commission of India and the Regulation and Administration of Electoral Politics: A Review - Basappa Ramappa Shindhure, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The Election Commission of India (ECI) is one of the most significant constitutional bodies entrusted with ensuring free, fair, and transparent elections in the world’s largest democracy. Since its inception in 1950, the ECI has acted as the guardian of democratic values by regulating electoral processes, overseeing political parties, and safeguarding voters’ rights. This article examines the role of the ECI in regulating and administering electoral politics in India. It evaluates the institutional framework, legal provisions, and mechanisms through which the Commission functions. Furthermore, it reviews challenges such as money power, muscle power, criminalization of politics, fake news, and electoral malpractices, alongside recent innovations like electronic voting machines (EVMs), Voter Verifiable Paper Audit Trails (VVPAT), and digital voter outreach. The study employs a qualitative and descriptive methodology, drawing upon constitutional provisions, secondary literature, government reports, and recent case studies. Findings reveal that while the ECI has emerged as a credible institution, it faces mounting challenges in ensuring electoral integrity amidst changing political dynamics. The article concludes by suggesting reforms such as strengthening the autonomy of the Commission, enhancing transparency in campaign finance, stricter enforcement of the Model Code of Conduct (MCC), and increased voter awareness initiatives.
Keywords: Election Commission of India; Electoral Politics; Democracy; Regulation; Electoral Administration; Model Code of Conduct; Electoral Reforms